Something in these hills : the culture of family land in southern Appalachia - Coggeshall, John M. (The University of North Carolina Press, 2022)
"What is the 'something in these hills' that ties mountain families to family land in the southern Appalachians? This ethnographic examination challenges contemporary theory and explores two interrelated themes: the duality of the southern Appalachians as both a menacing and majestic landscape and the emotional relationship to family land characteristic of long-term residents of these mountains"--